Sociodemographic characteristics of youth in a trauma focused‐cognitive behavioral therapy effectiveness trial in the city of Philadelphia. Issue 4 (24th December 2019) - Last, Briana S.; Rudd, Brittany N.; Gregor, Courtney A.; Kratz, Hilary E.; Jackson, Kamilah; Berkowitz, Steven; Zinny, Arturo; Cliggitt, Lauren P.; Adams, Danielle R.; Walsh, Lucia M.; Beidas, Rinad S.
Abstract: While randomized controlled trials of trauma‐focused cognitive behavioral therapy (TF‐CBT) have demonstrated efficacy for youth with posttraumatic stress disorder, TF‐CBT effectiveness trials typically show attenuated outcomes. This decrease in effectiveness may be due to the differences in sociodemographic characteristics of youth in these trials; youth in efficacy trials are more often white and middle‐income, whereas youth in effectiveness trials are more often racial/ethnic minorities, of low socioeconomic status (SES) and live in high crime neighborhoods. In this study—drawn from an effectiveness trial of TF‐CBT in community mental health clinics across Philadelphia—we describe the sociodemographic characteristics of enrolled youth. We measured neighborhood SES by matching participants' addresses to American Community Survey data from their Census tracts, housing stability using the National Outcomes Measurement System, and neighborhood violence using police department crime statistics. Our results suggest that the majority of youth presenting for TF‐CBT in mental health clinics in the City of Philadelphia live in poor and high‐crime neighborhoods, experience substantial housing instability, and are predominantly ethnic and racial minorities. Thus, youth presenting for treatment experience significant racial and socioeconomic adversity. We also explored the association between these characteristics and youth symptom severity upon presenting for treatment. These factors were not associated with youth symptom severity or overall mental health functioning in our sample (with small effect sizes and p  > .05 for all). Implications for future research, such as the need for efficacy and effectiveness trials to more fully characterize their samples and the need for pragmatic trials are discussed.